Perpetual Motion Generator Prototype - Raja Iskandar Zulkarnain; Ahmad Zainuddin Azmi; Muhammad Syahmi Danial Khairul Anwar; Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2024)
The use of conventional energy sources, such as fossil fuels, has had a negative impact on the environment. Additionally, their limited availability is a growing concern as their consumption continues to rise. Farmers in Ayer Hitam face challenges in protecting their crops and repelling pests, with current methods being costly and generating inadequate income. These farmers also lack access to reliable energy sources, relying instead on expensive fuel-powered generators. This study focuses on the rotating wheel rim and holder project, aiming to analyze its performance in generating energy for a light bulb. The results and discussion section will provide a comprehensive analysis, quantifying the amount of energy produced and discussing the system's efficiency, limitations, challenges, and potential improvements. The design's practicality and sustainability, particularly for off-grid farming, will be emphasized. The prototype experiment compared the average speed of the rotating wheel with the theoretical value, highlighting the design's capabilities. The perpetual motion generator prototype proved successful in providing a continuous energy supply for the light bulb. Success factors included minimizing air resistance, reducing friction between components, and precise calibration of the magnet source. To enhance power output, the integration of an auxiliary capacitor circuit is necessary. This circuit acts as an energy storage unit, accumulating surplus power during peak performance and discharging it when power demand exceeds the generator's capacity. This approach ensures a stable and continuous power supply, making the generator suitable for applications requiring higher wattage levels. In conclusion, this study provides valuable insights into the feasibility and challenges associated with perpetual motion generators. While acknowledging skepticism within the scientific community, this achievement encourages further exploration and inspires researchers to push the boundaries of energy generation.